2019
DOI: 10.1177/1049732319857058
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling to Capture the Health Care Perspective of People Who Are Homeless

Abstract: Utilizing a hermeneutic philosophical approach, the researchers explored the perceptions and experiences of people who are homeless in Mobile, Alabama, receiving health care and interacting with health care providers. Using the voice of the participants, discussions among the researchers, and supporting literature reinforcing key concepts, a framework was created illustrating the lived experience. The following themes were identified: social determinants of health, compromised systems, professionalism, dehuman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Along the same lines, another recent study in Alabama (USA) reported de-humanized attention along with a lack of commitment and professionalism on the part of medical staff. This contributed to diminishing confidence in the medical system among homeless individuals [39,43].…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, another recent study in Alabama (USA) reported de-humanized attention along with a lack of commitment and professionalism on the part of medical staff. This contributed to diminishing confidence in the medical system among homeless individuals [39,43].…”
Section: Discussionmentioning
confidence: 99%
“…The need for providers to convince homeless patients that they were respected emerged with particular force, reinforcing what others have also found. For example, patients who are homeless often find themselves feeling dehumanized and convinced that they are not welcome or respected, both situations that hinder care (Moore-Nadler et al, 2019). It is particularly important that clinicians communicate both trust and respect, especially when caring for patients who are highly stigmatized in settings where mistrust by clinicians is often part of the culture (Merrill et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In one, 17 homeless interviewees highlighted commitment, respect, trust, and inclusion as important to their overall satisfaction (McCabe et al, 2001). Other qualitative work has typically assessed perceptions of health care in general, or mental health services, without focus specifically on primary care, even though targeted investments in primary care for homeless populations date to 1984 and include both the United States Department of Health and Human Services and VA (McCallum et al, 2019; Moore-Nadler et al, 2019; Pahwa et al, 2019; Zlotnick et al, 2013). To inform the development and evaluation of an effective model of homeless-focused primary care, our team conducted an in-depth, qualitative exploration of key domains of primary care that may be important to patients, guided by landmark reports from the Institute of Medicine (IOM) that sought to define key components of primary care and quality of care (Committee on the Future of Primary Care for the Institute of Medicine, 1996; Institute of Medicine Committee on Quality of Health Care in America, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PEH and those unstably housed are often designated as "hard to reach" by the medical and scientific community, and as such, little research exists into interventions that explore infectious disease treatment programs in this population (Hanlon et al, 2018). While recent research has explored therapeutic relationships between homeless individuals and healthcare providers (Moore-Nadler et al, 2020), the need for culturally sensitive treatment studies is important to understand, explain, and tailor to the complex sociocultural factors that create the conditions for both low participation and low HCV completion rates among PEH with curative HCV interventions (Hanlon et al, 2018;Lambert et al, 2019;Surey et al, 2019). Addressing the sociocultural factors from within a PEH community context is foundational to any HCV intervention among homeless adults (Dombrowski et al, 2016).…”
Section: Culturally Sensitive Methodology To Inform the Design Of An Hcv Intervention Trialmentioning
confidence: 99%